ChemInform Abstract: Synthesis of Functionalized Tetrahydropyridazines via Catalyst‐Free Self [4 + 2] Cycloaddition of in situ Generated 1, 2‐Diaza‐1, 3‐dienes. Issue 46 (27th October 2016) - Zhang, Zhimin; Zhang, Li; Chen, Qingqing; Lu, Tao; Zhou, Qingfa
Abstract: The treatment of chlorides (I) with K2 CO3 gives rise to tetrahydropyridazines (II) in high yields.